The Use of Granular Cyclopentanone as Alternative to Artificial Source of Carbon Dioxide in Improved Passive Outdoor Host Seeking Device (POHD) - Stella T. Kessy; Bruno A. Nyundo; Ladslaus L. Mnyone; Issa N. Lyimo (The Scientific World Journal)
Reliable sources of CO2 that are relatively cheap, obtainable, and easy to sustain are immediately required for scaling up of odor-baited mosquito surveillance and control devices. Several odor-baited devices are in the pipeline; however, their scale-up against residual malaria transmission, particularly in resource poor areas, is limited by the unavailability of reliable sources of CO2 and reliance on electrical power sources among other factors. We evaluated the use of granular cyclopentanone as an alternative to artificial or yeast fermentation-produced CO2 in passive outdoor host seeking device (POHD). Experiments were conducted against semifield reared An. arabiensis within the semifield system (SFS) at Ifakara Health Institute. Mosquitoes were tested against odor-baited POHDs augmented with yeast fermentation-produced CO2, granular cyclopentanone, attractive blends (Mbita or Ifakara), or their combinations. An insecticide, bendiocarb, was a killing agent used as a proxy for marking the mosquitoes visit the POHDs. Relative attractiveness of different treatment combinations was compared based on the proportion of dead mosquitoes that visited the POHD. The POHD augmented with granules of cyclopentanone alone was attractive to An. arabiensis as much as, or more than, POHDs augmented with yeast fermentation-produced CO2. The POHD baited with CO2 attracted more mosquitoes than those POHDs baited with synthetic blends alone; when these blends are combined with CO2, they attracted more mosquitoes than individual blends. More importantly, such POHDs baited with cyclopentanone attracted far greater proportion of mosquitoes than the POHD baited with either Mbita or Ifakara blend alone. The granular cyclopentanone strongly enhanced/potentiated the attractiveness of POHD baited with Mbita blends against mosquitoes compared to that of POHD baited with Ifakara blend. Moreover, the granular cyclopentanone retained its residual activity against An. arabiensis for up to 2 months after application particularly when used in combination with Mbita blend. In conclusion, this study demonstrates that cyclopentanone granules have the potential to substitute sources of CO2 in outdoor-based surveillance and control devices, thus warranting evaluation of such alternative under realistic field conditions.